Multivariate scaling methods and the reconstruction of social spaces Papers in honor of Jörg Blasius - Barth, Alice; Leßke, Felix; Atakan, Rebekka; Schmidt, Manuela; Scheit, Yvonne (Verlag Barbara Budrich, 2023)
This edited volume assembles contributions of leading scholars in the fields of statistical methods and applications in the social sciences. Multivariate scaling methods for categorical data, in particular correspondence analysis, are used to extract the most important dimensions from complex data tables and to visualize relationships in the data. The volume treats recent statistical developments, methodological considerations, and empirical applications. A special emphasis is placed on multiple aspects of space and their sociological significance: the reconstruction of "social spaces" with statistical methods, illustrations of spatial relations involving proximity, distance and inequality, and concrete interactions in urban neighbourhoods. The edited volume is meant to honour the lifetime achievements of Prof. Jörg Blasius (Chair of Sociology/ Empirical Research Methods, Bonn).